2015 IEEE International Symposium on Technologies for Homeland Security (HST) 2015
DOI: 10.1109/ths.2015.7225312
|View full text |Cite
|
Sign up to set email alerts
|

Computing on Masked Data to improve the security of big data

Abstract: Organizations that make use of large quantities of information require the ability to store and process data from central locations so that the product can be shared or distributed across a heterogeneous group of users. However, recent events underscore the need for improving the security of data stored in such untrusted servers or databases. Advances in cryptographic techniques and database technologies provide the necessary security functionality but rely on a computational model in which the cloud is used s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…CryptDB replicates most DBMS functionality with a performance overhead of under 30% [15]. This approach has been extended to NoSQL key-value stores [157], [158]. Arx is built on a NoSQL keyvalue store called mongoDB [63].…”
Section: Current Protected Search Databasesmentioning
confidence: 99%
“…CryptDB replicates most DBMS functionality with a performance overhead of under 30% [15]. This approach has been extended to NoSQL key-value stores [157], [158]. Arx is built on a NoSQL keyvalue store called mongoDB [63].…”
Section: Current Protected Search Databasesmentioning
confidence: 99%
“…It has been found that majority of the paper in this topic is just a discussion manuscript, so this paper discusses about 5 most relevant implementation work that has been carried out in last 5 years. Gadepally et al [21] have presented a cryptography based approach to encipher a big data while performing analysis of it. The system uses D4M (Dynamic Distributed Dimensional Data Model) for processing the unstructured data and have used Galois Field Cryptography with AES encryption approach.…”
Section: Research Work In Bamentioning
confidence: 99%
“…However, these advantages also create a single point where adversaries may try to attack the confidentiality, integrity and/or availability of sensitive information stored or being processed [26].…”
Section: Data Qualitymentioning
confidence: 99%
“…The sensitivity of data being processed in the cloud is increasing; and it is possible to make use of cryptographic advances to secure processing in the cloud to address a growing veracity of big data [26].…”
Section: Data Qualitymentioning
confidence: 99%